Sexual orientation and the European Convention on Human Rights: What of the "L" in LGBT?. Issue 3 (3rd July 2019) - Hodson, Loveday
Abstract: The European Court of Human Rights (ECtHR) has long been celebrated for its role in advancing LGBT rights. This article adopts an intersectional feminist approach in order to critically examine the trajectory of the Court's LGBT case-law from a gendered perspective. In doing so, it foregrounds the portrayal, experience and, indeed, invisibility of lesbian applicants. Adopting an intersectional approach that considers the gender dimension of sexual orientation claims provides a somewhat different perspective on the struggle for LGBT rights before the ECtHR and suggests that lesbian voices and experiences have been marginalized and excluded in the struggle for LGBT rights.